Battery-equivalent DC Supply from Leakage Current: PV to Transformer-less Inverter Topology - M. N. H. Khan; K. J. Ahmad; M. S. Zahan; M. N. Hasan (Institute of Advanced Engineering and Science, 2016)
Solar panels are highly used for electricity generation, which can be gotten through switching-based transformer-less inverters. Hence, grid system with no galvanic-isolation, is taking the peak level in the world, which is effective and delivers power with enhanced efficiency. The PV generation presented here is for stand-alone system installed in remote areas on when and as the resulting power gets connected to electronic load installation instead of being tied to the grid. In this paper will be discussed the use of leakage current. Transformer-less inverter topology for exploring the issue of common mode (CMV) voltage development, which can be utilized as a Battery-Equivalent DC Supply after adding on places as when found suitable for such installations.